Revenue neutral trade reform with many households, quotas and tariffs - Anderson, James E. 1943- (NBER working paper series, 1997)
Government budget balance forces the endogenous use of distortionary tax instruments" when an exogenous reform is implemented. The aggregate efficiency of such reforms is based" on comparisons of simple summary measures of the Marginal Cost of Funds of the various tariff" or quota changes with the Marginal Cost of Funds of the alternative taxes Benefit of Government supplied goods. The aggregate efficiency of tariff liberalization is" dubious, while quota liberalization is more likely to be efficient. Social welfare rises with" aggregate efficiency unless distribution effects are perverse. Plausible sufficient conditions for" non-perverse distributional effects are provided. The results frame a diagnostic method for" sensitivity analysis in evaluations of trade and tax policies.